Papers of the Conference on Genetics of Aging and Longevity 2012 - Elena G. Pasyukova; Alexey Moskalev (Frontiers Media SA, 2014)
The 2nd International Conference "Genetics of aging and longevity" took place 22-25 April, 2012 in the main building of Russian Academy of Sciences, Moscow, Russia. Top gerontologists and geneticists from 25 countries around the world discussed the current problems in many areas related to the genetics of longevity and mechanisms of aging. This Research Topic is aimed to provide a collection of articles based on the talks, reports and experimental outcomes related to the topics of the conference: "Epigenetic Changes Associated with Longevity", "Hormones and Aging", "Proximal and Cellular Mechanisms of Aging", "Nutrient Signaling, Stress Resistance and Longevity", "Identifying Longevity Genes by Mutational, QTL and Association Mapping", "Fundamental Biological Processes Central to Aging", "Interventions to Extend Lifespan and Promote Healthy Aging", "Longevity: Meta-Analysis and Informatics Approaches". Participants of the Conference submitted 20 papers belonging to Original Research Papers, Review Articles (Including Mini Reviews), Opinion and Perspective Papers. All of the submitted manuscripts were peer-reviewed by excellent Frontiers Review Editors and prepared for publication by highly efficient Frontiers team, and it is a pleasure to thank them all for their work and dedication.
English
Keywords: Aging; Genetics; geroprotectors; evolution; epigenetics